Loop capital : funding growth in an investment bank - White, Gregory, (SAGE knowledge. Cases., 2016)
Jim Reynolds Jr. founded Loop Capital in 1997 as an investment bank specializing in bond sales for municipalities. Ten years later, with 13 offices and almost 100 employees, Loop Capital was a national company and had brokered more than $800 billion of underwritings in equity, tax-exempt, and taxable fixed income markets. In the process of building its municipal finance and equity trading businesses, Loop Capital had developed close relationships with a number of government officials, large institutional money managers, and corporate executives. These customers began asking Loop Capital for help with other financial services, leading the firm to build corporate finance, tax-exempt, and taxable fixed-income platforms so it could offer a wider array of investment services.